Growth and maturity status of young elite and sub-elite tennis players - Sögüt, M.; Ödemis, H.; Durmus, D. (Coaching and Sport Science Review, 2023)
The purposes of this study were to determine the growth and maturity status of young competitive tennis players and to examine their associations with national rankings. The participants were 36 male and 34 female players who competed in the U14 national team selection tournament in 2022. They were divided into three groups according to their results and entries as national players (n = 8), main draw players (n = 31), and qualifying players (n = 31). Ages at peak height velocity and growth status were calculated. Regardless of gender, the mean height and body mass percentiles of players were above the 60th centile. In girls, the results indicated that both national and main draw players were significantly more advanced in maturation (p< 0.05) and had higher body mass indexes (p< 0.05) than qualifying players. In boys, no significant differences were observed among the three groups for all variables. Correlation results showed that maturity status was the most correlated (p< 0.01) variable in girls. No significant relationships between rankings and other variables were obtained for boys. These results suggest that physical size and advanced maturity should be taken into consideration in the selection and identification of youth elite female tennis players.